Tapeséré Akorang Mabbasa Ogi - Teguh Arafah (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2018)
Many indigenous Muslims compose a book of interpretation with different types of languages ​​and methods used. Then came the mention of